Proceedings of the International Conference on Physiological Computing Systems 2014
DOI: 10.5220/0004928701730178
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Three-Dimensional Kinematic Biofeedback on the Performance of Scapula-focused Exercises

Abstract: Abstract:Three-dimensional (3D) kinematic biofeedback can help identify scapular movement disorders and assist the subjects' motor relearning process by facilitating changes in physiological and biomechanical function through real-time knowledge of performance and result during or immediately after a task execution. This study assessed the effectiveness of 3D kinematic biofeedback on the quality of the scapula-focused exercises execution, and motor learning transfer during shoulder flexion and a daily activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…However, conventional clinical assessments are typically conducted once every three to four months. Recent studies suggested real-time kinematic feedback could improve the quality of rehabilitation exercises as it monitors patient's execution of commands (Antunes et al, 2014;Kim, Kim, & Kim, 2017). Real-time feedback also improves patients' motivation by making their progress tangible (Kim, Kim, & Kim, 2017), which can be achieved with the help of clinical robots.…”
Section: Clinical Assessmentsmentioning
confidence: 99%
“…However, conventional clinical assessments are typically conducted once every three to four months. Recent studies suggested real-time kinematic feedback could improve the quality of rehabilitation exercises as it monitors patient's execution of commands (Antunes et al, 2014;Kim, Kim, & Kim, 2017). Real-time feedback also improves patients' motivation by making their progress tangible (Kim, Kim, & Kim, 2017), which can be achieved with the help of clinical robots.…”
Section: Clinical Assessmentsmentioning
confidence: 99%